Analisis Sikap Politik Warga Muhammadiyah Ponorogo Dalam Pilkada 2015 - Harsono, Jusuf (Universitas Muhammadiyah Ponorogo, 2018)
Plurality of political attitudes of citizens Muhammadiyah Ponorogo in the elections in 2015 is an interesting phenomenon because almost all citizens and sympathizers of this organization gives full support to the partner Regent and Vice Regent promoted by the National Mandate Party. This study to find out more about political attitudes of citizens muhammadiyah shown in local elections (Election) Ponorogo. Moreover, the research also seek out further orientations are used as a handle by Muhammadiyah cadres and elite that are part of a successful team. Informants in this study is regular and elite members or directors of the Muhammadiyah organization spread over several districts. Data collection in studies using interviews and documentation. The final goal of this study was to determine the political direction of Muhammadiyah then it could be a foundation in nominating candidates for the next general election